POJĘCIE RYZYKA I JEGO UMIEJSCOWIENIA (LOKALIZACJI) W PRAWIE UBEZPIECZEŃ GOSPODARCZYCH - Fuchs, Dariusz (Zeszyty Prawnicze, 2017)
THE NOTION OF RISK AND ITS PLACEMENT IN THE COMMERCIAL INSURANCE LAW Summary The article presents the notion of risk in the act on insurance activity, the adoption of which constitues an example of the absorption acquis. It has been noticed that the notional dispersion of risk present in the Polish law is inevitable even if certain connotations may bring about some reservations. A specific example of an implementation of the community law is the concept of placement of risk, which has two main functions in the Polish legal system: it is a connecting factor indicating relevant norms of competence and it serves as legal limitations for the supervisory body within the community freedom of rendering services. A review of the Polish legislation in this respect made the author to formulate remarks de lege ferenda.